1990
DOI: 10.1126/science.2125368
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Clonal Elimination of Functional T Cells

Abstract: A major mechanism for generating tolerance in developing T cells is the intrathymic clonal deletion of T cells that have receptors for those self antigens that are presented on hematopoietic cells. The mechanisms of tolerance induction to antigens not expressed in the thymus remain unclear. Tolerance to self antigens can be generated extrathymically through the induction of clonal nonresponsiveness in T cells with self-reactive receptors. A second mechanism of extrathymic tolerance was identified: clonal elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
85
0
3

Year Published

1991
1991
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 191 publications
(90 citation statements)
references
References 58 publications
2
85
0
3
Order By: Relevance
“…The lower representation of Vb5 and Vb11 among donor T cells later on suggests that peripheral deletion might occur in our chimeras, as previously shown [26], possibly by additional antigen encounter on peripheral cells [27]. On the other hand, variability in Vb representation, usually important within chimeras [23], might also account for the lower Vb representation observed.…”
Section: Discussionsupporting
confidence: 51%
“…The lower representation of Vb5 and Vb11 among donor T cells later on suggests that peripheral deletion might occur in our chimeras, as previously shown [26], possibly by additional antigen encounter on peripheral cells [27]. On the other hand, variability in Vb representation, usually important within chimeras [23], might also account for the lower Vb representation observed.…”
Section: Discussionsupporting
confidence: 51%
“…DNA from each of the sorted cell populations was isolated and subjected to DNA gel electrophoresis. The results of gel electrophoresis shown in Figure 2, lanes (6)(7)(8), (Fig. lC), whereas HO-High cells (R2) clustered as high FSC-low SSC events (Fig.…”
Section: Isolation and Identification Of Apoptotic Cellsmentioning
confidence: 92%
“…It is well known that anti-CD3 antibodies can induce apoptotic cell death in thymocytes (5, 11,12,17), in T-cell hybridomas (6,14,20), and in established T-cell lines (9,21). Although the response of mature T cells to anti-CD3 antibodies typically results in T-cell proliferation (l), some recent studies have demonstrated that mature T cells undergo apoptosis and clonal deletion in response to TCRaIP and TCRP antibodies (7,131. The ability of anti-CD3 to induce some T cells to proliferate while triggering programmed cell death in others remains the subject of intense investigation.…”
mentioning
confidence: 99%
“…4). At birth (5,6,9,11,(19)(20)(21)(22)(23)(24). Likewise, EL singly transgenic mice did not develop spontaneous autoimmunity in exocrine pan- creas.…”
mentioning
confidence: 99%